2022
DOI: 10.1186/s13102-022-00425-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical and technical demands of offence, defence, and contested phases of play in Australian Football

Abstract: Background This study compared the physical demands and effect of field location for different phases of play (offence, defence and contested), and examined the physical and technical demands of successful and unsuccessful phases of play during Australian Football matches. Methods Global positioning system (GPS) and technical performance data were collected from 32 male Australian Football players in one club over 19 games in the 2019 season. The G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It can be seen from Table 1 that, a total of 40 students were included in the study and were randomly divided into two groups, 20 in the experimental group and 20 in the control group, all of whom were boys, with an average age of 21.4 ± 0.9 years old, the mean values of the control group and the experimental group were 0.8 and 0.7, respectively, and the corresponding p value was 0.250; In terms of height, the mean values of the control group and the experimental group were 4.0 and 3.9, respectively, and the corresponding p value was 0.665; In terms of body weight, the mean values of the control group and the experimental group were 4.3 and 6.9, respectively, and the corresponding p value was 0.763; In terms of BMT, the mean values of the control group and the experimental group were 1.48 and 1.44, respectively, and the corresponding p value was 0.636; On the index of exercise years, the mean values of the control group and the experimental group were 1.1 and 1.3, respectively, and the corresponding p value was 0.254; In the special data, the p values of the control group and the experimental group were 0.723, 0.363, 0.212, 0.723, 0.677, and 0.723, respectively. 9 The corresponding p values of these six indicators were all greater than 0.05, and there was no significant difference between the control group and the experimental group in the six indicators of age, height, weight, BMI, years of exercise, and specialties.…”
Section: Resultsmentioning
confidence: 85%
“…It can be seen from Table 1 that, a total of 40 students were included in the study and were randomly divided into two groups, 20 in the experimental group and 20 in the control group, all of whom were boys, with an average age of 21.4 ± 0.9 years old, the mean values of the control group and the experimental group were 0.8 and 0.7, respectively, and the corresponding p value was 0.250; In terms of height, the mean values of the control group and the experimental group were 4.0 and 3.9, respectively, and the corresponding p value was 0.665; In terms of body weight, the mean values of the control group and the experimental group were 4.3 and 6.9, respectively, and the corresponding p value was 0.763; In terms of BMT, the mean values of the control group and the experimental group were 1.48 and 1.44, respectively, and the corresponding p value was 0.636; On the index of exercise years, the mean values of the control group and the experimental group were 1.1 and 1.3, respectively, and the corresponding p value was 0.254; In the special data, the p values of the control group and the experimental group were 0.723, 0.363, 0.212, 0.723, 0.677, and 0.723, respectively. 9 The corresponding p values of these six indicators were all greater than 0.05, and there was no significant difference between the control group and the experimental group in the six indicators of age, height, weight, BMI, years of exercise, and specialties.…”
Section: Resultsmentioning
confidence: 85%
“…After the completion of a match, the microsensor technology data were downloaded onto the proprietary software (Playertek Cloud). In-line with previous research (48,49), periods of BiP and successful offence and defence (Table 1) were identified through a timeline of events provided by Champion Data (Melbourne, Australia)-a commercial company that codes events with associated time stamps for the AF League (AFL) and WAFL-and manually entered on the microsensor technology data.…”
Section: Match Analysesmentioning
confidence: 99%
“…Maximum BiP phases (e.g., the one with the highest meters per minute) were then obtained for each of the 3 microsensor technology metrics for every player, in every game. Periods of successful offense and defense were cleaned in-line with previous research (49) by removing all phases where the player did not complete the full phase of play (e.g., were rotated off) and were then summed so that each player had a total for each phase in each match. Periods of successful offense and defense were then contextualized with technical data, based on previously described definitions, and expressed per minute of playing time (7,27):…”
Section: Match Analysesmentioning
confidence: 99%
See 2 more Smart Citations